Melatih Soft Skills Mahasiswa Melalui Program Kampus Mengajar Angkatan 3 Tahun 2022 di SDN 10 Ampenan - Hikmawati Hikmawati (Pascasarjana Universitas Mataram, 2022)
Soft skills are skills that must be possessed by 21st-century students in order to compete globally and be successful in the future. The purpose of this community service activity is to train students' soft skills through the Teaching Campus Program Batch 3 at SDN 10 Ampenan. The activity was carried out from March to May 2022 which took place at SDN 10 Ampenan, with a total of 5 students. Indicators of soft skills that are trained consist of 6 aspects, namely Confidence, Initiative, Creativity and Innovation, Communication, Cooperation, and Discipline. The assessment of student soft skills uses a scale of 4. The activity results show that the average soft skills of students are 22 which is very good criteria. The indicator of student soft skills that has the highest score is in the Confidence, Initiative, and Communication aspects of 20, while the lowest score is found in the Cooperation aspect of 15. The Teaching Campus Program is a program that plays an important role in training students' soft skills to be ready to enter the university. world of work in the 21st century. Therefore, the Campus Teaching program should still be held as a real effort by the government to improve the quality of education in Indonesia